2004
DOI: 10.1002/ijc.20105
|View full text |Cite
|
Sign up to set email alerts
|

Receptor for the globular heads of C1q (gC1q‐R, p33, hyaluronan‐binding protein) is preferentially expressed by adenocarcinoma cells

Abstract: Combinatorial Ig libraries with phage display allow in vitro generation of human Ig fragments without the need to maintain hybridomas in ongoing cell culture or to select circulating Ig from human serum. Identifying tumor-associated antigens on the surface of intact tumor cells, as opposed to purified proteins, presents a challenge due to the difficulty of preserving complex 3-D epitopic sites on the cell surface, the variable expression of antigens on different malignant cell types and the stereotactic interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
61
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 61 publications
7
61
1
Order By: Relevance
“…Although a direct functional link between these two proteins remains to be investigated more thoroughly, this observation suggests that the transient association of gC1qR with the cytoplasmic tail of MT1-MMP is likely to be involved in the mechanisms regulating presentation of the protease at the tumor cell surface where gC1qR expression has been shown to be enhanced in a tumor cell-specific manner (Rubinstein et al, 2004).…”
Section: Differential Cellular Localization Of Gc1qr May Dictate Its mentioning
confidence: 99%
See 2 more Smart Citations
“…Although a direct functional link between these two proteins remains to be investigated more thoroughly, this observation suggests that the transient association of gC1qR with the cytoplasmic tail of MT1-MMP is likely to be involved in the mechanisms regulating presentation of the protease at the tumor cell surface where gC1qR expression has been shown to be enhanced in a tumor cell-specific manner (Rubinstein et al, 2004).…”
Section: Differential Cellular Localization Of Gc1qr May Dictate Its mentioning
confidence: 99%
“…This hypothesis was put to the test by experiments in which a combinatorial immunoglobulin (Ig) library of 10 10 clones was first generated from the cDNA of primary breast adenocarcinoma cells (Rubinstein et al, 2004). Following subtractive panning, the library was enriched for Ig (Fab fragment) binding to intact adenocarcinoma cells and the resultant Fab was screened against a cDNA expression library generated from breast cancer cells.…”
Section: Differential Cellular Localization Of Gc1qr May Dictate Its mentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5] Many human tumors exhibit higher p32 expression levels than their nonmalignant counterpart tissues. [6][7][8][9] Depleting p32 in human cancer cells strongly shifts their metabolism from oxidative phosphorylation to glycolysis. 1 Consistently, p32 knockout causes mid-gestation lethality of knockout embryos and defects in oxidative phosphorylation.…”
mentioning
confidence: 99%
“…Mouse embryonic fibroblasts (MEFs) generated from p32 knockout embryos exhibited impaired ATP production and reduced mitochondrial membrane potential, which is in agreement with the observation that p32 silencing leads to increased mitochondrial fragmentation. 10,11 Notably, p32 was found to form protein complex with a variety of molecules 7,12,13 and has been suggested that it may act as a multifunctional chaperone protein. [12][13][14] ULK1 has a crucial role in mitophagy induction.…”
mentioning
confidence: 99%